Handbook of cognitive linguistics - Dąbrowska, Ewa, 1963-; Divjak, Dagmar (Handbücher zur Sprach- und Kommunikationswissenschaft,, 2015)
This handbook provides state-of-the-art overviews of the numerous subfields of cognitive linguistics written by leading international experts which will be useful for established researchers and novices alike. It is an interdisciplinary project with contributions from linguists, psycholinguists, and computer scientists which emphasizes the most recent developments in the field, in particular, the shift towards more empirically-based research.